Regulation of apoptosis through cysteine oxidation: implications for fibrotic lung disease - Janssen-Heininger, Yvonne M.W. (2010)
Tissue fibrosis is believed to be a manifestation of dysregulated repair following injury, in association with impaired reepithelialization, and aberrant myofibroblast activation and proliferation. Numerous pathways have been linked to the pathogenesis of fibrotic lung disease, including the death receptor Fas, which contributes to apoptosis of lung epithelial cells. A redox imbalance also has been implicated in disease pathogenesis, although mechanistic details whereby oxidative changes intersect with profibrotic signaling pathways remain elusive. Oxidation of cysteines in proteins, such as S-glutathionylation (PSSG), is known to act as a regulatory event that affects protein function. This manuscript will discuss evidence that S-glutathionylation regulates death receptor induced apoptosis, and the potential implications for cysteine oxidations in the pathogenesis of in fibrotic lung disease.